ANALISIS SWOT SEBAGAI DASAR DALAM PENENTUAN STRATEGI PEMASARAN - Dasururi, Rubait; Muzajjad, Ach.; Mubarok, Chilmy (eBA Journal: Journal Economics, Bussines and Accounting, 2018)
This study aims to determine and analyze the presence and position of meatballs effort based on SWOT analysis and determine the right marketing strategy for your business based on the results of SWOT analysis meatballs. This research uses descriptive qualitative approach. The data used is qualitative data with the use of primary data and secondary data sources. The data collection is done by the method, triangulation namely, observation, interviews, and documentation. Data were analyzed by using analysis SWOT checking the validity of the findings to confirm the data of the study subjects. The findings are based on analysis of business meatballs SWOT have factored into strengths, namely cow wearing original raw materials, the processing is done by the business owner so that the owner can control according to the standards set. Meatball business opportunities are increasing as the holiday sales increase in class and Idul Fitri, and has a loyal customer. Threats to business meatballs are many competitors with a similar business, price competition, rising raw material products, differentiation of products made by competitors.